Long‐term within‐season changes in the diet of Common Guillemot (Uria aalge) chicks at a North Sea colony: implications for dietary monitoring. (14th April 2022) - Harris, Michael P.; Albon, Steve D.; Newell, Mark A.; Gunn, Carrie; Daunt, Francis; Wanless, Sarah
Abstract : Over four decades (1982–2019) there were pronounced within‐season changes in the proportion of a key prey species (Lesser Sandeel Ammodytes marinus ) in Common Guillemot Uria aalge chick diet. As Sandeels became scarcer their occurrence was largely confined to the early part of the chick period. Consequently, the mean annual proportion of Sandeels was poorly estimated if sampling occurred within a short time window, particularly if this was early or late in the season. Within‐season variation is rarely considered in diet monitoring but our results highlight the need for further analyses across other species and sites to develop a deeper understanding of how best to optimize sampling protocols.